TRENDS IN CHANGES OF LEADING BACTERIAL CAUSATIVE AGENTS OF PELVIC INFLAMMATORY DISEASES IN WOMEN DURING 2013-2017 - Lisyana, T.A.; Salmanov, A.K.; Katsalap, O.N.; Ponomarova, I.G.; Krishchuk, S.Y. (World of Medicine and Biology, 2020)
Over the last decade, both in the world and in Ukraine, there has been a significant increase in the incidence of pelvic inflammatory disease in women. The purpose of the study was to evaluate the trends in the leading bacterial causative agents of pelvic inflammatory diseases during 2013-2017 in 554 women in the disease exacerbation. The results of the examination of patients for the period from 2013 to 2017 indicate: inoculation rate fluctuations of individual bacterial inflammatory factors in different years of the study, increasing vaginal contamination of patients with opportunistic pathogens and a significant frequency of contamination with fungi of the genus Candida on the background of protective bacteria deficiency. The structure of vaginal bacteriological flora in women was dominated by S. epidermidis (haem+), E. faecalis, S. haemolyticus, E. coli and Kl. pneumoniae, which frequency and quantitative indices of inoculation in the observation trends tended to increase. The obtained data indicate the need for microbiological monitoring of changes in pathogens of pelvic inflammatory diseases in order to timely identify violations of microecology and prescribe rational therapy regimens.
Keywords: trends in changes; bacterial causative agents; pelvic inflammatory diseases